Analysis Of Indonesian Language Textbook Content Junior High School Grade Viii With Curriculum 2013 - Fikri, Khufaifatul; Pocaan, Jean Pauline Trilles-; Hai, Lê Thị Thanh (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the conformity of the content of two Indonesian language textbooks used in Grade VIII at MTsN 3 Indramayu with the 2013 curriculum, particularly in relation to the basic competencies outlined in the syllabus. Methodology: This study applied a descriptive qualitative method. The data sources were two Indonesian textbooks: Marbi Mahir Berbahasa Indonesia and Buku Bahasa Indonesia (published by Erlangga and Yhama Widya). Data were collected through document analysis, interviews, and observation, and evaluated using textbook assessment criteria such as academic integrity, detail, and coverage. Main Findings: The results indicate that the conformity between the textbooks and the 2013 curriculum syllabus was only 25% in terms of content. However, based on textbook quality criteria, both books met 80% of the standards, suggesting they remain usable as supplementary learning materials despite their partial misalignment with the curriculum. Novelty/Originality of this study: This study offers an in-depth evaluation of how current textbooks align with national curriculum standards, highlighting gaps in implementation. It advances existing knowledge by identifying specific areas where textbook content fails to meet curricular expectations, offering practical input for educators, authors, and policymakers.